PSYCHOLOGY OF DAKWAH A RHETORICAL APPROACH TO THE SURAH AL-NAHL 125 - Ahmad Rifai; Salahudin Salahudin (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2020)
This article discusses the dynamics of da'wah in social change. In the last two decades, humanitarian cases, social changes and political systems in very different orders of modern society have been responded by Muslim communities with very diverse attitudes. The stigma of radical Islam, extremism and jihadists is a central issue. Instead of improving that image, many demands have arisen. Among of the demands of issue that must be reviewed include our interactions with other parties (non-Muslims), our views, and our attitude towards them. This research uses maudhu’i’s method. This paper is more a reflection in the process of internalization of the holy book which focused on surah al-Nahl [16]: 125 with the latest rhetoric of da'wah.